FRI0186 Concomitant csdmards influence clinical response to tnf inhibitors only in overweight patients with axial spondyloarthritis. (12th June 2018) - Hernández-Breijo, B.; Navarro-Compán, V.; Martínez-Feito, A.; Jochems, A.; Villalba, A.; Peiteado, D.; Kneepkens, E.L.; Nozal, P.; Wolbink, G.J.; Rispens, T.; Pascual-Salcedo, D.; Balsa, A.; et al.
Abstract : Background: In patients with axial spondyloarthritis (axSpA), the use of conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs), such as methotrexate (MTX) and sulfasalazine (SSZ), as well as the body mass index (BMI) have been associated with circulating TNFi levels. Recently, BMI has also been associated with TNFi clinical response but csDMARDs have not shown any significant clinical improvement for axial manifestations 1 . However, no study has assessed in the same population the influence of both factors -csDMARDs and BMI- on drug serum levels and clinical response Objectives: To investigate the influence of csDMARD and BMI on circulating drug levels and clinical response to TNFi therapy in axSpA patients Methods: A 1 year follow-up prospective observational study with two cohorts (Madrid and Amsterdam) including 180 axSpA patients treated with standard doses of infliximab (41%) or adalimumab (59%). Laboratory and clinical parameters were collected every 6 months. Patients were stratified by BMI: normal-weight (18.5–24.9 kg/m 2 ) and overweight-obesity (>25.0 kg/m 2 ). TNFi trough levels were measured by capture ELISA 2 . Clinical response to TNFi was defined as ▵BASDAI ≥2. The association between concomitant csDMARDs and BMI with drug levels and clinical response to TNFi at 1 year was analysed through multivariate log-regression models (odds ratio and 95% CI). The presence of significant interactions between covariates was tested and all models were adjusted for age, gender, HLA-B27, disease duration, TNFi-type (for drug levels) and baseline BASDAI and CRP (for clinical response) Results: Seventy-nine out of 180 patients (44%) received concomitant csDMARDs (MTX 14%, SSZ 20% and MTX +SSZ 10%), 78 (43%) patients were normal-weight and 102 (57%) overweight-obese. Mean (SD) age and disease duration was 47(13) and 11(9) years respectively, 59% were males, 73% HLA-B27 +and 78% had r-axSpA. Concomitant csDMARDs (OR: 3.82; IC 95%: 1.06–13.84) and being overweight-obese (OR: 18.38; IC 95%: 2.24–150.63) were independently associated with serum TNFi drug presence. Furthermore, a significant interaction between csDMARDs and BMI with clinical response was found. While the use of concomitant csDMARD contributed positively to achieve clinical response in overweight-obese patients (OR: 7.86; IC 95%: 2.39–25.78), no association was found for normal-weight patients (OR: 1.10; 0.33–3.58). Additionally, sensitivity analysis using remission status and ASDAS were performed and showed results along the same line Conclusions: In patients with axSpA, TNFi drug persistence is positively influenced by the use of concomitant csDMARDs and especially by being normal-weight. However, TNFi clinical response is associated with the use of concomitant csDMARDs only in overweight-obese, but not in normal-weight patients. Based on this, the use of concomitant csDMARDs in patients with axSpA could be beneficial in overweight patients References: [1] van der Heijde D, et al. Ann Rheum Dis. 2017;76(6):978–991. [2] Pascual- Salcedo D, et al. Rheumatology (Oxford) . 2011;50(8):1445–52. Disclosure of Interest: None declared